A multi-dimensional analysis on microeconomic factors of China's industrial energy intensity (2000–2017). (December 2020) - Zhang, Chi; Su, Bin; Zhou, Kaile; Sun, Yuan
Abstract: Reducing energy intensity is the key point to solve the contradiction among economic development, energy constraints and environmental pressure in China. Considering microeconomic factors, this paper extends decomposition and attribution models, and analyses the drivers of China's industrial aggregate energy intensity (AEI) at the regional/sectoral level. The results show that AEI decreased by 49% during 2000–2017. At the regional level, most provinces presented negative contribution on regional energy intensity effect. The AEI decline was attributed to the drop of greatest negative effect of R&D efficiency in Liaoning . The increase in investment intensity and R&D intensity lead to an increase in AEI, largely owning to Shandong and Liaoning, respectively. At the sectoral level, the AEI decline can be mainly explained by the inhibition effect of energy intensity and R&D efficiency. However, this negative contribution was greatly offset by the R&D intensity effect. The investment intensity showed a positive impact in AEI increase, and smelting and pressing of ferrous metals sector was the main contributor. Regional and sectoral investment structure effect shifted from increasing to decreasing AEI over the study period. Based on the results, targeted policy recommendations are proposed to further decrease the China's industrial AEI in the 14th FYP period. Highlights: A regional and sectoral analysis is conducted to study China's industrial AEI. Extended IDA and attribution approaches considering techno-factors are used. R&D efficiency and investment intensity are crucial factors influencing AEI. The contributions of provinces and sectors through impact factors vary greatly. Policy should encourage the rational use of R&D expenditure and investment.